Transformasi Lembaga Keuangan: Menggali Potensi dan Manfaat Beralih Dari Bank Konvensional ke Bank Syariah - Nihayatul Maskuroh; Asep Dadan Suganda; Kurnia Akbar (Banque Syar'i: Jurnal llmiah Perbankan Syariah, 2023)
This study explores the planned transformation of financial institutions from conventional banks to Islamic banks, focusing on respondent perceptions, interests, and preferences. Using a quantitative approach, data were collected through surveys, in-depth interviews, and official document analysis at the Faculty of Islamic Economics and Business (FEBI) at Universitas Islam Negeri Sultan Maulana Hasanuddin (UIN SMH Banten). The results show that most respondents are highly interested in transacting through Islamic financial institutions (LKB Syariah), with 83.0% expressing high interest, 15.3% expressing moderate interest, and only 1.7% expressing low interest. Additionally, the survey results related to the interest in transforming financial institutions from conventional to Islamic banks reveal that most respondents (87.0%) support FEBI UIN SMH Banten's initiative for this transformation. In comparison, 13.0% are not interested in switching to LKB Syariah. Furthermore, the most preferred bank among respondents when switching to LKB Syariah is Bank Syariah Indonesia (BSI) at 76.3%, Bank Muamalat Indonesia (BMI) at 11.3%, and BTN Syariah at 9.6%. The remaining 2.8% of respondents chose other banks.